The Meeting Point of Neo-Sufism and School Counselors Competencies - Ridwan, Ridwan; Sutoyo, Anwar; Mansur, Ali (Jurnal Kajian Bimbingan dan Konseling, 2020)
Neo-sufism is the recent Sufi movement that actively develops society. Historically, sufism has brought forth arif billâh individuals who have great faith and devotion to Allah, excellent pedagogical competence, as well as social and professional skills. This study aims to construct the meeting point between neo-sufism character and school counselor competence. It was carried out using a qualitative approach with the Hermeneutic analysis from Paul Ricoeur. The data was obtained from documents and interviews. The results reveal the meeting point between neo-sufism character and four counselors competencies. Makrifatullah (depth comprehension of God) character is linear with pedagogical and personality competence. Prioritizing other people (itsar) and noble (futuwwah) character are in line with social competence; meanwhile, creative-productive (intajiyyah) character is in accordance with professional competence. Therefore, neo-sufism character transforms counselors’ competencies to be more significant and meaningful.